Possible Application of Successful International Models with Regard to Digitalization of State Services: The Case of the Health Care System in the Republic of Azerbaijan - Mammadova, Jamila; Abdullayev, Huseyn; Amiraslanova, Mehin (ADA University, 2022)
The main goal of this study is to analyze one of the most pressing issues in Azerbaijan, the issue of the healthcare system, and identify weaknesses in the system from the perspective of digital governance. To come up with feasible solutions, descriptive research design, specially interviews together with an analysis of experiences around the globe were run. As a result of a comprehensive investigation, best international practices were utilized into Azerbaijan’s healthcare system - especially the ones which were in line with the terms of the five principles such as equity, equality, feasibility, efficiency and effectiveness. Analyzing the gaps in the current healthcare system and the global trends around the world, it is necessary for Azerbaijan to establish a universal integrated health record (EHR system). Moreover, an e-prescription portal, as part of the e-health database should be launched. Training for citizens should be conducted in order to increase digital literacy and is of vital importance.
Keywords: Public and International Affairs; E-Governance -- Azerbaijan.; E-Health -- Azerbaijan.; Healthcare -- Azerbaijan.